All that glitters is not gold: the impact of the Nutri-score label on food with geographical indication - Alice Stiletto; Luigi Cembalo; Samuele Trestini (Agricultural and Food Economics)
Abstract The European Union is discussing the introduction of a mandatory front-of-pack label to address the rise in nutrition-related diseases. The Nutri-Score (NS) is the most supported candidate in the EU, despite some controversies exist. Specifically, the policy behind the NS system (i.e., the Farm to Fork Strategy—F2F) appears to conflict with the geographical indication (GI) policy, as the same products (GIs) are promoted for their superior quality by the GI policy and frequently classified as products to be avoided by the NS system. Moreover, the NS system, by encouraging the food industry to reformulate products to improve their nutritional quality, places the GIs in a disadvantageous position, due to their strict product specification. To explore the interactions between these two policies, this paper assesses the effect of the NS on retail prices of both GI and non-GI products in the French market, where this system is widely used. A hedonic price analysis was conducted on 254 raw hams (score D or E) through the estimation of a quantile regression model. Results highlight that the presence of the NS decreases the retail price of raw hams, limited to the high-priced segments. Interestingly, the negative effect is consistent for both GI and non-GI hams, suggesting that the GI label does not mitigate the impact of the NS.